18F‐FDG PET/CT features of immune‐related adverse events and pitfalls following immunotherapy. Issue 4 (22nd February 2022) - Cherk, Martin H; Nadebaum, David P; Barber, Thomas W; Beech, Paul; Haydon, Andrew; Yap, Kenneth S
Summary: 18 F‐FDG PET/CT scanning is routinely performed to stage and evaluate the treatment response in many malignancies. Immunotherapy is a rapidly growing treatment option for many cancers, and both clinicians and imaging specialists need to be familiar with 18 F‐FDG PET/CT imaging characteristics unique to patients on this type of treatment. In particular, many immune‐related adverse events (irAEs) can be detected on 18 F‐FDG PET/CT and early accurate identification is critical to reduce treatment related morbidity and incorrect interpretation of malignant disease status. This pictorial essay reviews frequently encountered irAEs in clinical practice and their appearances on 18 F‐FDG PET/CT along with a brief discussion on pseudoprogression and hyperprogression.